Unveiling young learners’ perceptions in learning English using a learning module in a community engagement project - Abu Bakar, Siti Zarikh Sofiah; Mohd Yusof, Fairuz Husna; Azrae, Munirah; Amat, Dia Widyawati; Sumery, Zuraidah; Othman, Diana; Sarijari, Haniza (Universiti Teknologi MARA, Kedah, 2024)
A concern has been raised on poor academic performance in English subject among school pupils in Malaysia. The number of class periods in current school timetable is viewed as insufficient to produce proficient English speakers. Thus, activities that encourage learners’ participation in English language activities and enhance interests among the learners should be actively conducted. This research explores young learners’ perceptions towards their participation in an English learning module that emphasises on the aspects of speaking, spelling and writing. The one-day activity involved six facilitators from the Academy of Language Studies, UiTM Cawangan Johor took place at a primary school located in Johor. The research involved 27 standard one learners. A set of questionnaires was shared to all the students and the data were recorded and statistically analysed for frequencies. An interview was conducted to gather the learners’ feedbacks on their experiences learning the English module. The data were then analysed using thematic analysis. The findings suggest that this academic-based module offers positive learning experiences to the participants and is viewed as a supportive and dynamic learning environment for the learners. This study highlights the important role of community engagement in language education. Future research is recommended to explore the effects of such models on learners’ English proficiency and performance.